Gingival squamous cell carcinoma - Amit Walvekar; Jagadish Pai; Gana Gangamma; Shashidara Raju; Annaji Sreedhar; M A Uthappa (Wolters Kluwer Medknow Publications, 2017)
Oral squamous cell carcinoma (OSCC) is the most common epithelial malignancy affecting the oral cavity. The most common sites for the development are lateral surface of tongue and floor of mouth; the least common sites are soft palate, gingiva, and buccal mucosa. Gingival squamous cell carcinoma can mimic a multitude of oral lesions and enlargements, especially those of inflammatory origin. In addition, predisposing and presenting factors are different from those of other OSCCs. Careful examination as well as routine biopsy are crucial for accurate diagnosis.